1981
DOI: 10.1111/j.1432-1033.1981.tb05072.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Topology and Glycosylation on the Fate of Heterologous Secretory Proteins Made in Xenopus Oocytes

Abstract: Secretory proteins made in Xenopus luevis oocytes under the direction of heterologous messenger RNA are modified, topologically segregated and exported. Thus the oocyte may serve as a useful surrogate secretory system and we have studied some of the factors governing access to the export pathway. Unglycosylated chicken ovalbumin, synthesized and trapped in the cytosol, is not secreted but glycosylated ovalbumin, found sequestered within vesicles, is exported from oocytes. However, ovalbumin, which is transferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

1981
1981
1989
1989

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…Both approaches demonstrate that the synthesis of membrane and secretory proteins is tightly coupled to sequestration and core glycosylation at the level of the endoplasmic reticulum, and that these mechanisms are common to many cell types [ 5 ] . Recent studies on the mechanisms of secretion using Xenopus oocytes also demonstrate that intracellular events subsequent to sequestration must be common to different cell types, and that the posttranslational addition of prosthetic groups, such as the glycosylation of known glycoproteins, is not required to ensure secretion [6].…”
mentioning
confidence: 99%
“…Both approaches demonstrate that the synthesis of membrane and secretory proteins is tightly coupled to sequestration and core glycosylation at the level of the endoplasmic reticulum, and that these mechanisms are common to many cell types [ 5 ] . Recent studies on the mechanisms of secretion using Xenopus oocytes also demonstrate that intracellular events subsequent to sequestration must be common to different cell types, and that the posttranslational addition of prosthetic groups, such as the glycosylation of known glycoproteins, is not required to ensure secretion [6].…”
mentioning
confidence: 99%
“…Glycosylation by the oocyte system can be inhibited with tunicamycin, an antibiotic which inhibits asparagine-dependent glycosylation. Colman et al (8) found that tunicamycin-treated oocytes produced a smaller form of ovalbumin than is found in vivo. A similar result has been obtained with the G I storage protein of bean.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, glycosylation accompanies cleavage of the signal peptide, but as has been shown by Bielinska, Blobel, and Colman, cleavage can occur when glycosylation is inhibited (2,6,8). Prevention of glycosylation in vitro has been accomplished by isolating signal peptidase activity from membranes by treatment with detergent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The half-lives recorded (Table 1) The influence of secondary modification of protein stability can be studied using pairs of proteins differing only in, for example, their degree of N-glycosylation or phosphorylation. Tunicamycin-treated oocytes [8] Fig. 1 C: in the experiment shown in B exported frog proteins are swamped by chicken proteins.)…”
Section: The Influence Of Detachable Signal Sequences and Secondary Mmentioning
confidence: 99%